Improved biosynthesis and recovery of polyhydroxyalkanoates from Comamonas sp. EB172 - Ab. Razak, Nor asma (2013)
Polyhydroxyalkanoates (PHA) is a potential biodegradable polymer which can be used to replace a petrochemical synthetic polymer. PHA is synthesised when bacteria are exposed to a surplus of carbon and limited nitrogen. Under these con- ditions, cells are unable to grow but they do accumulate carbon-based polyesters. The objectives of this study were to improve PHA production by Comamonas sp. EB172 through fed-batch and repeated fed-batch, to characterise the effect of freeze-drying and oven-drying on cell and PHA and to improve recovery of PHA from Comamonas sp. EB172 using chemicals (solvent and sodium hydroxide) and biological (protease) methods. From this studies, Comamonas sp. EB172 which is novel locally isolated strain produced 6-9 g/L DCW, 77-86% PHA content, 5- 12 mol% 3HV and 172-177 kDa Mw from fed-batch and 4-11 g/L DCW, 50-64% PHA content, 9-13 mol% 3HV and 832 kDa Mw from repeated fed-batch fermen- tation.Thus, through repeated fed-batch fermentation, high Mw could be obtained which gave new properties for different applications. The oven-dried changed the chemical structure, developed crystal and changed the thermal properties of P(3HB-co-3HV) compared to freeze-dried P(3HB-co-3HV). Meanwhile, membrane cell of oven-dried become shrink, agglomerate to each other and become akes compared to membrane cell of freeze-dried which become etched due to freezing and vacuum freezing. More than 90% purity of P(3HB-co-3HV) and P(3HB-co-3HHX) were obtained using acetone, chloroform, methanol and n-hexane as precipitate solvents. In addition, NaOH and protease from ginger, Zingiber officinale Roscoe were chosen as alternative recovery methods as they're environmental friendly, cheap and could be used to reduce chloroform effect to operator health and environment. Thus, the improvement on NaOH method were done include different NaOH concentrations (0.1, 0.2, 0.3, 0.6, 0.8, 1 and 2 N), different residence time of cells (63, 87 and 111 h), initial drying cell conditions (wet broth, wet pellet, freeze-dried and oven-dried) and washing (distilled water, 20% and 100% ethanol). The protease which is highly specific to degrade cell membrane was successfully extracted and precipitated using acetone precipitation gave 256 U/mg with 60% recovery yield. The effect of cell concentration (5,10 and 20 g/L), incubation times and washing (distilled water, 20% and 100% ethanol) were done for P(3HB-co-3HV) recovery using protease. The best combination of freeze-drying cells for NaOH and protease are using 1N NaOH, incubation 1 hour with 100% cell concentration, centrifuged, washing two times with 20% ethanol and 0.02% cell concentration, incubation with 256 U/mg specific activity enzyme protease for 50 min, centrifuged and washing two times with 100% ethanol. Both methods gaves more than 90% P(3HB-co-3HV) purity and are comparable with recovery using chloroform and n-hexane with different fold Mw composition, thermal and physical properties. The properties of PHA are highly dependent upon their mode of fermentation and recovery techniques; hence, biodegradable polymer having a wide range of properties which can be used in different applications.